The Influence of Origami on Spatial Abilities in Mathematics Learning - Nugraha, Candra; Prabawanto, Sufyani; Kurniawati, Ririn (PRISMA, 2025)
The essential mathematical ability related to geometric perception is spatial ability. Through this ability, one can develop geometric reasoning abilities in everyday life. In some literature, spatial ability is closely related to various applied fields in life. One way to develop and hone this ability is through the art of origami paper folding. In several studies, it has been found that origami can enhance students' spatial abilities at various educational levels. Origami is the art of folding paper that is utilized for teaching basic geometric shapes through folds that form simple structures, which can serve as a bridge for students to understand how the objects they fold are formed. This origami folding can be used to train and enhance the spatial abilities of students from various educational levels. Teaching origami can foster and develop students' enthusiasm in learning mathematics, especially geometry. Origami has a positive correlation with mathematics learning outcomes in the classroom, particularly regarding geometry topics.